Time trends in the prevalence of diagnosed sialolithiasis from Taiwanese nationwide health insurance dental dataset - Yu-Hsun Wang; Yi-Tzu Chen; Yu-Wei Chiu; Hui-Chieh Yu; Yu-Chao Chang (Elsevier, 2019)
Background/Purpose: Sialolithiasis, the so-called salivary gland stone, is a condition forming salivary calculi within a salivary gland or ducts. Little is known about the epidemiological survey of sialolithiasis in Taiwanese population. In this study, we conducted an age-period-cohort (APC) analysis evaluating the prevalence of sialolithiasis. Materials and methods: A retrospective study was conducted to analyze the registered database compiled by the Taiwanese National Health Insurance Research Database from 1996 to 2013. The APC analysis was performed to investigate the effects of age, diagnosis period, and birth cohort with sialolithiasis. Results: We found that the prevalence of sialolithiasis varied from 1.4 (105) to 2.3 (105). The mean age ±standard deviation with sialolithiasis from 1996 to 2013 was 37.7 ± 18.5 and 46.2 ± 18.6 years old, respectively. The prevalence was higher among male than female (RR: 1.10; 95% CI: 1.05-1.15, p < 0.001). The age >65 group had higher risk compared to age <40 group (RR: 2.27; 95% CI: 2.13-2.43, p < 0.001). The relative risk for sialolithiasis demonstrated significant age effect (p < 0.001). The relative risk for sialolithiasis did not show the significant period effect (p = 0.742). The relative risk for sialolithiasis demonstrated significant cohort effect (p = 0.01). The relative risk for sialolithiasis demonstrated significant APC effect (p = 0.002). Conclusion: Form this nationwide population-based database, the prevalence of sialolithiasis occurs more frequently in male than in female. In addition, the relative risk for sialolithiasis demonstrated the significant APC effects. Keywords: Sialolithiasis, Taiwan, Prevalence, Nationwide population-based study, Age-period-cohort